2016
DOI: 10.1007/s10826-016-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Establishment of Health Promoting Relationships: A Descriptive Synthesis of Anorexia Nervosa Research

Abstract: Qualitative values that address personal and interpersonal dimensions are often overlooked in research that examines mental well-being among young patients with anorexia nervosa. The aim of this review was to identify and describe factors that promote and impede the relationships between nurses and the children, adolescents and young adults who are diagnosed with anorexia nervosa and also to explore and describe how those relationships benefit the patients' processes toward increased health and well-being. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
3
34
0
8
Order By: Relevance
“…Our meta‐ethnography highlighted coping strategies which appear conducive to HCP and service‐user wellbeing. The emphasis on connecting with common humanity, and being humbly open to learning and support, are similar to the findings of Salzmann‐Erikson and Dahlén (), and Seah et al (). What is novel is the notion of mindfully drawing on this humanity and humility to adopt a compassionate approach that eschews the rigidity of avoidance or blame.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our meta‐ethnography highlighted coping strategies which appear conducive to HCP and service‐user wellbeing. The emphasis on connecting with common humanity, and being humbly open to learning and support, are similar to the findings of Salzmann‐Erikson and Dahlén (), and Seah et al (). What is novel is the notion of mindfully drawing on this humanity and humility to adopt a compassionate approach that eschews the rigidity of avoidance or blame.…”
Section: Discussionsupporting
confidence: 85%
“…This is the first meta‐ethnography to focus exclusively on HCPs' lived experiences of working with people with EDs. As well as supporting the findings of previous reviews (Salzmann‐Erikson & Dahlén, ; Seah et al, ; Sibeoni et al, ; Thompson‐Brenner et al, ), it yields new insights regarding the experiences of this work, and approaches to managing challenges in clinical practice. Findings from 37 studies, which spanned 21 years and were of moderate to high quality, were synthesized to produce a key concept of “Coping with caring without curing.” The meta‐ethnography describes how those working in ED services are limited in their capacity to help, which creates a painful dissonance that can impact on enjoyment of the job, perceptions of service users, and working alliances.…”
Section: Discussionsupporting
confidence: 82%
“…For example, some studies have found anxiety in ASD to be positively correlated with intelligence quotient (IQ), whereas others have found no relationship or, in some cases, a negative correlation [18, 23, 24, 25•]. Furthermore, other studies have found that only specific anxiety symptoms (e.g., generalized, separation, and panic-related worries) were associated with higher IQ in individuals with ASD [23].…”
Section: Prevalence Of Anxiety and Ocd In Autismmentioning
confidence: 99%
“…That is, to be aloof or detached from consumers is not conducive to interpersonally sound nursing care. Adolescents who have received care for AN place value on interpersonal supportive relationships with healthcare professionals (Salzmann‐Erikson & Dahlén ; Sibeoni et al . ).…”
Section: Discussionmentioning
confidence: 99%